Grafting Cu(II)-5-amino-1H-tetrazole complex on magnetic graphene oxide as an efficient magnetically recoverable catalyst for the synthesis of N-benzyl-N-aryl-5-amino-1H-tetrazoles - Gharoubi, Hanieh; Nasrollahzadeh, Mahmoud; Khorsandi, Zahra; Nobre, Marcos A.L. [UNESP]; Choi, Sungkyun; Kruppke, Benjamin; Ali Khonakdar, Hossein (Elsevier, 2023)
In this study, a new approach has been developed for the synthesis of a novel catalyst based on Cu(II)-5-amino-1H-tetrazole complex immobilized on the surface of graphene oxide-modified magnetic nanoparticles (GO/Fe3O4@Tet-Cu(II)) by 3-chloropropyltrimethoxysilane ((MeO)3Si-PrCl) as a linker. The synthesis of GO/Fe3O4@Tet-Cu(II) was confirmed by FT-IR (Fourier transform-infrared spectroscopy), XRD (X-ray diffraction), VSM (Vibrating sample magnetometer), TG-DTG (Thermogravimetry and differential thermogravimetry), EDS (energy dispersive X-ray spectroscopy), elemental mapping, and TEM (transmission electron microscopy). GO/Fe3O4@Tet-Cu(II) showed high catalytic activity in the synthesis of N-benzyl‐N‐aryl‐5‐amino‐1H‐tetrazoles via the reaction of N-benzyl-N-arylcyanamides and NaN3 in DMF solvent at 120 °C in a short reaction time with good yields. The catalyst can be recycled for five runs without losing its efficiency and demonstrates excellent chemical stability and high potential for practical synthetic applications. N-Benzyl‐N‐aryl‐5‐amino‐1H‐tetrazoles were characterized using FT-IR and NMR analyses. The present strategy could help design and synthesize future catalysts for organic synthesis.
Keywords: Cu(II) complex; Graphene oxide; Heterogeneous catalyst; Magnetic catalyst; N‐Benzyl‐N‐aryl‐5‐amino‐1H‐tetrazoles